Lange on Mathematical Explanation, Grounding, and the Divergence Thesis - Mohammad Maarefi (Crítica)
Mark Lange has defended the view that mathematical explanation and grounding explanation diverge. In this paper, I argue that at least one type of grounding relation is immune to his criticisms. After fixing a minimal separatist theory of ground, I show that his arguments mostly rely on another thesis about grounding (I’ll call it “atomic grounding thesis”), which is not supported. Furthermore, a second attempt at using purity is not entirely satisfactory.